On small war : Carl von Clausewitz and people's war - Scheipers, Sibylle (Oxford University Press, 2018)
Carl von Clausewitz has long been interpreted as the paradigmatic thinker of major interstate war. This book challenges this assumption by showing that Clausewitz was an ardent analyst of small war and integrated many aspects of his early writings on partisan warfare and people's war into his magnum opus, 'On War.' It reconstructs Clausewitz's intellectual development by placing it in the context of his engagement with the political and philosophical currents of his own times - German Idealism, Romanticism, and Humanism. The central question that Clausewitz and his contemporaries faced was how to defend Prussia and Europe against Napoleon's expansionist strategy.